Social Sciences E-Module Contains Balinese Folklore Based on Pancasila Student Profiles - Sandat, Desak Putu Monika; Wulandari, I Gusti Agung Ayu (Universitas Pendidikan Ganesha, 2024)
Implementing social studies learning for grade 1 elementary school is still not optimal in absorbing material concepts and people's values in social studies lessons. One of the causes is the low quality of teaching modules teachers own. This research aims to develop a social studies e-module containing Balinese folklore based on Pancasila student profiles for grade 1 students in elementary schools. This research uses the Dick and Carey development model, which consists of 10 stages. The subject of this research is to use individual trials of 3 students and small group trials of 9 people. This research applies a post-test-only method with data collection methods using questionnaires and multiple-choice objective tests. Data analysis involves qualitative and quantitative descriptive analysis techniques. The research showed that the e-module obtained a very good classification with media validity of 80%, social studies content validity of 95%, design validity of 97.22%, language validity of 90%, individual trials of 91.67%, and small group trials amounting to 91.67%. The effectiveness calculation shows a significance value of 0.000 (< 0.05), confirming a significant difference in student understanding between classes that use e-modules containing Balinese folklore with Pancasila student profiles and classes that use regular e-modules. Thus, it is known that the new features in the e-module have proven effective in improving the quality of the learning process. This research can be used as a parameter for e-module development to support the feasibility and effectiveness of implementing learning for elementary school students.